READINESS ON DENTAL TRAUMA IN FEDERALLY QUALIFIED HEALTH CENTERS. WHY IT MATTERS? - Valverde Ingersoll, Yessenia (2025)
Dental Trauma refers to injuries to the lips, teeth, gums and supporting bone due to accidents such as falls, injuries, or assaults. (1) Readiness for treating dental trauma is of upmost importance in Federal Qualified Health Centers (FQHCs) which serve medically underserved populations, often including children, low-income individuals, and those without regular access to dental care. (2) Although dental trauma may not always be the top priority in primary care settings, its consequences can be severe and long-lasting, particularly when treatment is delayed. (3) For the vulnerable populations, FQHCs often act as the first point of contact for urgent dental needs. (4) Early intervention is critical to preventing complications that may include infection, pain, and even tooth loss. (3)